The suitability of Bukit Ekspo Lake for water based recreational purpose based on water quality - Zulbaharin, Asmaq Fikriyah (2018)
Water quality can be used to assess the health of ecosystems, safety for human contact, and water supply. It is important for household, agricultural, industrial and also recreational purposes. Therefore, a study on water quality status of Bukit Ekspo Lake has been carried out to investigate the suitability of the study area to conduct recreational activities and the ability of the lake to purify waste water. The in-situ samples of water pH and Dissolved Oxygen (DO) were taken in situ while samples for Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia-cal Nitrogen (NH3N) and Total Suspended Solid (TSS) were analyzed in laboratory. These parameters were measured every week for six weeks period at six stations. Results showed that water quality status at Bukit Ekspo is in Class 3 which indicates that the Bukit Ekspo Lake needs intensive treatment and it is not suitable for recreational activities. Moreover, the lake cannot purify by itself where the Water Quality Index (WQI) at inlet was greater than the outlet. The findings from this study showed Bukit Ekspo Lake are not suitable for water based recreation activities and cannot purify waste water. Therefore the management of this park needs to undertake intensive treatment to improve the water quality of this lake in order to be suitable for water-based recreational activities.